Differences In Pregnancy Care Service Visits Before And During Covid 19 Pandemic In Midwifery Independent Practice - Rosalinna Rosalinna (Poltekkes Kemenkes Surakarta, 2021)
Background: Pandemic COVID-19 has prompted the government to implement a social distancing policy. This also applies to pregnant mother to come to health workers unless there are signs of pregnancy. This study aims to know the influence of pregnancy services before and after the COVID-19 pandemic. Methods: This is Mixed Method study with the sample was a midwife who carried out the Midwifery Independent Practice or “Praktek Madiri Bidan” (PMB) in Sragen Regency, Central Java Province. In-depth interviews were conducted with 10 informants. Statistical test using Paired T test, qualitative data using transcription and categorization Results: The average number of visits to maternity care at PMB was 117.0 (21.83) visits per month in the two months prior to the COVID-19 pandemic, only 67,6 (7,63) monthly visits for two months during COVID 19 pandemic. Obtained ρ value 0,000 which means there is a difference in Pregnancy Care Service Visits before and during the COVID 19 pandemic at PMB Sragen Regency, Central Java. There are two themes in the results of the qualitative study, namely the anxiety of midwives in providing midwifery services during the COVID-19 pandemic and the Protocol for Pregnancy Care Services during the COVID-19 Pandemic. Conclusions: There are differences in pregnancy services during the COVID-19 pandemic. The government is expected to be able to socialize technical guidelines for pregnant women in accessing services on pregnancy and prevention of COVID-19.